HEALTHY EATING IMPROVEMENT COURSE FOR SCHOOL COOKS - Margareth Xavier da Silva; Débora Pinto de Oliveira Santos; Rogério Mello Gonçalves Filho; Anna Paola Trindade Rocha Pierucci; Cristiana Melo Porto Pedrosa (Universidade do Estado do Rio de Janeiro, 2017)
Schools are considered to be an optimal space for health education. The meals offered to students are an opportunity for learning and socialization. In this context, the role of the cooks goes beyond the preparation of meals, as they often need to plan the menu and replace some food items. Objective: This study promoted a Professional Development Course with cooks from public schools in Xerém district, in Duque de Caxias, Rio de Janeiro, Brazil, in order to broaden knowledge about healthy eating. Methods: The course was attended by 26 school cooks, and it was taught for four consecutive days in classrooms of the Federal University of Rio de Janeiro, at the Institute of Nutrition Josué de Castro. Previous and later evaluations about knowledge of healthy eating were performed by means of games: the Healthy Dish Game and the Pyramid Food Game. The proposed activities consisted of a lecture, development of educational materials by the participants, and a cooking workshop. The software R and the Shapiro-Wilk tests were used to evaluate if the data has a normal distribution, and the Wilcoxon test (p <0.05) was used to evaluate whether or not learning took place after intervention. Results: The participants' scores had significant improvement in the evaluation of games after the educational activities had been performed. Conclusion: The professional improvement course promoted knowledge among most participants, as shown by the results of the games used in their evaluation, i.e., with improved scores. Activities involving the whole school community are suggested in order to promote better quality of life and health within this group. DOI: 10.12957/demetra.2017.22712